Opioid use is associated with incomplete capsule endoscopy examinations: a systematic review and meta-analysis - Momani, Laith Al; Alomari, Mohammad; Bratton, Hunter; Boonpherg, Boonphiphop; Aasen, Tyler; Kurdi, Bara El; Young, Mark (Translational Gastroenterology and Hepatology; Vol 5 (January 2020): Translational Gastroenterology and Hepatology, 2019)
Background: Capsule endoscopy (CE) is a non-invasive imaging modality designed to evaluate various small bowel pathologies. Failure to reach the cecum within the battery lifespan, termed incomplete examination, may result in inadequate testing and possibly delayed therapy. Several studies have attempted to evaluate the association between CE completion and opioid use. However, their results are conflicting. The aim of this meta-analysis is to evaluate the previously published literature on the association between opioid use and CE completion. Methods: We performed a comprehensive literature search in PubMed, PubMed Central, Embase, and ScienceDirect databases from inception through June 1, 2018, to identify all studies that evaluated the association between CE completion and opioid use. We included studies that presented an odds ratio (OR) with a 95% confidence interval (CI) or presented the data sufficient to calculate the OR with a 95% CI. Statistical analysis was performed using the comprehensive meta-analysis (CMA), version 3 software. Results: Five studies with a total of 1,614 patients undergoing CE in the inpatient (IP) and outpatient (OP) setting were included in this study, 349 of which had an incomplete CE (21.6%). The pooled OR for CE completion is 0.50 (95% CI: 0.38–0.66, I2=36.9%) in opioid users compared to non-users. No publication bias was found using Egger’s regression test. Conclusions: Our results indicate that patients on opioids are significantly less likely to have a complete CE examination compared to non-users. To our knowledge, this study represents the first meta-analysis to assess this association.